Simultaneous Qualitative and Quantitative Analyses of Triterpenoids in Ilex pubescens by Ultra‐High‐Performance Liquid Chromatography Coupled with Quadrupole Time‐of‐Flight Mass Spectrometry. Issue 2 (18th September 2017) - Cao, Di; Wang, Qing; Jin, Jing; Qiu, Maosong; Zhou, Lian; Zhou, Xinghong; Li, Hui; Zhao, Zhongxiang
Abstract: Introduction: Ilex pubescens Hook et Arn mainly contains triterpenoids that possess antithrombotic, anti‐inflammatory and analgesic effects. Quantitative and qualitative analyses of the triterpenoids in I. pubescens can be useful for determining the authenticity and quality of raw materials and guiding its clinical preparation. Objectives: To establish a method for rapid and comprehensive analysis of triterpenoids in I. pubescens using ultra‐high‐performance liquid chromatography coupled to electrospray ionisation and quadrupole time‐of‐flight‐mass spectrometry (UPLC‐ESI‐QTOF‐MS), which will also be applied to evaluate the contents of nine triterpenoids among root, root heartwood and root bark of I. pubescens to judge the value of the root bark to avoid wastage. Methods: UPLC‐ESI‐QTOF‐MS data from the extracts of I. pubescens in negative mode were analysed using Peakview and Masterview software that provided molecular weight, mass errors, isotope pattern fit and MS/MS fragments for the identification of triterpenoids. The quantification of nine investigated compounds of I. pubescens was accomplished using MultiQuant software. Results: A total of 33 triterpenoids, five phenolic acids, two lignans and a flavonol were characterised in only 14 min. The total content of the nine compounds in the root bark was generally slightly higher than that of the root and root heartwood, which has not been reported before. Conclusion: The developed UPLC‐ESI‐QTOF‐MS method was proven to be rapid and comprehensive for simultaneous qualitative and quantitative analyses of the characteristic triterpenoids in I. pubescens . The results may provide a basis for holistic quality control and metabolic studies of I. pubescens, as well as serve as a reference for the analysis of other Ilex plants. Copyright © 2017 John Wiley & Sons, Ltd. Abstract : Ilex pubescens Hook et Arn. mainly contains triterpenoids that possess antithrombotic, anti‐inflammatory and analgesic effects. The established UPLC‐ESI‐QTOF‐MS method was successfully applied for simultaneous qualitative and quantitative analyses of triterpenoids in I. pubescens . A total of 33 triterpenoids were characterised, and the contents of nine triterpenoids among root, root heartwood and root bark of I. pubescens were finally determined, respectively. The results may provide a basis for holistic quality control and metabolic studies of I. pubescens .